The Influence of Sustainable Raw Material Availability and Environmentally Friendly Image on Competitive Advantage: The Mediating Role of Product Innovation - Hasan, Umar; Zulianto, Wahyu; Usman, Osly (Golden Ratio of Data in Summary, 2025)
This research takes a look at how product innovation acts as a mediator between the availability of sustainable raw materials, green brand image, and competitive advantage. One of the top distributors of cosmetic raw materials with worldwide sustainability certification, PT. Redachem Indonesia was the site of this investigation. One hundred people working in the cosmetics sector in the Jabodetabek region were surveyed using a standardized questionnaire. In order to analyze the data, the research used Structural Equation Modeling with the Partial Least Square (SEM-PLS) method. Product innovation is positively impacted by the availability of sustainable raw materials and a green brand image, according to the research. While the availability of raw sustainable raw materials does not significantly affect competitive advantage, an green brand image can. Product innovation not only mediates the connection between the two factors but also has a substantial effect on competitive advantage. These findings highlight how the cosmetics sector may increase its competitive positioning via innovation and environmental responsibility.